Educational Activities at University Museums and art Galleries as the European Tradition - Stepanskaya, Tamara Mikhaelovna (International Review of Management and Marketing, 2016)
A generalized description of the process of formation and development of museums and art galleries in the structures of higher education is presented in the article, focusing on universities. Ancient origins of traditions of museums and galleries organization at European universities are noticed; a brief overview of the historiographical works of the founders of the European museum pedagogy is presented; the influence of the European tradition in the development of Russian art in the late XIX - early XX centuries is shown. The article addresses the issues of the excursion work’s methods of organization and content, emphasizes the importance of the perception of an artwork, starting with the aesthetic contemplation. It notes the special experience of the Russian Academy of Arts in the use of academic museums as custodians of educational funds, as educators and means of formation of art culture of students and visitors of exhibitions; the modern experience of art galleries, particularly in the Altai State University, is briefly presented. Keywords: museum, gallery, exhibition, excursion, museum pedagogy, museum dialogue JEL Classifications: I20; I26; Z11